Remmittances and microfinance: reflections on global public goods - Cabezas , Rhina; Carballo de la Riva, Marta (Revista Española de Desarrollo y Cooperación, 2023)
The interaction between microfinance, migration and global public goods reveals the existence of new edges of study within microfinance by linking it to other fields with potential national, regional and international impacts. The article presents examples of this triangulation and identifies new lines of thought that allow the study of microfinance from a broader perspective.